Traffic Congestion Analysis: Case Study of Babakan Road Segment in Majalengka City - Muhammad Ridwan Nurrohman; Mohamad Taufik (Fakultas Teknik Sipil dan Perencanaan, 2025)
Major cities in Indonesia, including Majalengka, are facing significant problems related to traffic congestion. Babakan Road is one of the significant congestion points in the city of Majalengka. Jalan Babakan in the City of Majalengka, during peak hours, one of the busiest roads in Majalengka experiences traffic congestion. This congestion can cause exhaust emissions and queues on the roads. Most roads in the city of Majalengka experience traffic congestion due to the imbalance between population growth, the number of vehicles, and the underdeveloped road infrastructure. This imbalance is caused by the imbalance between population growth, the number of vehicles, and road development. This study aims to determine the impact of traffic congestion on Babakan Road in Majalengka City. This research will use the MKJI 1997 rules as the main reference or foundation to measure and assess congestion needs. In this study, surveys and observations are used to collect data. For primary data, it consists of the number of vehicles passing by, Microsoft Excel 2021, and Traffic Counter software. Secondary data is MKJI 1997. For the data on the highway segment, it consists of a two-lane, two-way road (2/2 UD). This research focuses on studying speed and density to help determine the average vehicle speed and average vehicle density. Regarding the results of the Babakan road study. Low traffic congestion levels usually occur during the day, while high traffic congestion levels usually occur in the morning and evening. Narrow roads, many vehicles, intersections, commuter mobility, and a limited number of public transport are some of the causes of congestion on Jalan Babakan. To address this congestion, there are several alternatives, such as increasing road capacity, increasing the number of public transportation, limiting the number of private vehicles, and setting age restrictions for drivers passing through Jalan Babakan.